Approach to the Evaluation and Treatment of Venous Thromboembolism in Pregnancy - Brenner, Benjamin; Grandone, Elvira; Makatsariya, Alexander; Khizroeva, Jamilya; Bitsadze, Victoria; Tretyakova, Maria (Seminars in Reproductive Medicine, 2021)
Thrombosis in pregnancy is a major cause of maternal and fetal morbidity and mortality. Risk stratification of venous thromboembolism (VTE) during pregnancy is complex. The hypercoagulability observed in pregnant women can reduce bleeding during childbirth, but may cause thrombosis especially in the presence of additional prothrombotic risk factors such as antiphospholipid antibodies or genetic thrombophilic defects. The availability of large datasets allows for the identification of additional independent risk factors, including assisted reproductive technologies (ARTs), endometriosis, and recurrent pregnancy loss. Data on the risk of VTE linked to COVID-19 in pregnant women are very limited, but suggest that infected pregnant women have an increased risk of VTE. Current guidelines on the prevention and treatment of VTE in pregnancy are based on available, albeit limited, data and mainly present expert opinion. Low-molecular-weight heparins (LMWHs) are the mainstay of anticoagulation to be employed during pregnancy. Administration of LMWH for VTE treatment in pregnancy should be based on the personalized approach, taking into account a weight-based adjusted scheme. During gestation, due to physiological changes, in women at high risk of VTE, monitoring of anti-Xa activity is performed to ensure adequate LMWH dosing. As for the treatment duration for pregnant women with acute VTE, guidelines suggest that anticoagulation should be continued for at least 6 weeks postpartum for a minimum total duration of therapy of 3 months.
Keywords: venous thromboembolism; pregnancy; thrombophilia; LMWH; COVID-19